Pengaruh Citra Perusahaan, Iklan dan Kualitas Layanan terhadap Keputusan Nasabah Memilih Produk Tabungan IB Amanah di BPRS Al Salaam Amal Salman Cabang Bandung - Putri Zafira; Renita Sugiarti (Ma'soem University, 2022)
The background of this research is the company's image, advertising and service quality to the development of the number of iB amanah savings customers at BPRS Al Salaam Amal Salman Cabanng Bandung. This research was conducted to find out how the influence of company image, advertising and service quality on customer decisions on choosing iB Amanah savings products at BPRS Al Salaam Amal Salman Bandung Branch both partially and simultaneously. The object studied in this study is iB Amanah savings customers related to the company's image, advertising, service quality, and customer decision to choose iB Amanah savings products at BPRS Al Salaam Amal Salman Bandung Branch. The method used is the associative quantitative method, with primary data through questionnaires and other supporting through library studies, observations and interviews. Data processing uses statistics with the help of the IBM SPSS Statistic 23 application. The results show that partially the corporate image variable (XI) has a significant effect on customer decisions (Y) by 49.1% or tcount > ttable (6,283 > 2,022), advertising variable (X2) has a significant effect on customer decisions (Y) by 56 ,3% or tcount < ttable (7,271 < 2,022), service quality variable (X3) has a significant effect on customer decisions (Y) by 82,9% or tcount > ttable (14,078 > 2,022). Simultaneously the variables of corporate image (X1), advertising (X2) and service quality (X3) affect the customer decision variable (Y) which is 84.6% or Fcount > Ftable (71.302>2.84).